Consumer Perception and Acceptance of Green Marketing Practices in Emerging Economies: A Systematic Literature Review (International Journal of Scientific Research in Science and Technology, 2025)
This study examines consumer perception and acceptance of green marketing practices in emerging economies through a structured systematic literature review. With increasing environmental concerns and the growing importance of sustainability, green marketing has emerged as a key strategy for influencing consumer behaviour and promoting eco-friendly consumption. The study analyzes 30 research papers published between 2020 and 2024, supplemented by selected foundational studies to provide theoretical grounding. The findings reveal that environmental awareness positively influences consumer perception; however, it does not necessarily translate into actual purchasing behaviour. Price sensitivity, particularly in emerging economies, is identified as a major barrier limiting the adoption of green products. Additionally, trust and credibility play a crucial role, as concerns related to greenwashing significantly affect consumer acceptance. Marketing communication, especially through digital platforms, is found to enhance awareness and shape consumer attitudes, although its effectiveness depends on transparency and accuracy. The study also highlights the persistent attitude–behaviour gap, indicating that positive consumer attitudes toward sustainability do not always lead to consistent purchasing decisions. Furthermore, the findings emphasize the influence of socio-economic and cultural factors in shaping consumer behaviour in emerging markets. This research contributes to the existing literature by providing a comprehensive and integrated understanding of the determinants influencing consumer perception and acceptance of green marketing practices. The study offers practical implications for marketers and policymakers to design effective strategies that promote sustainable consumption. Future research should focus on sector-specific studies, rural consumer behaviour, and cross-country comparisons to further advance this field. The study uniquely integrates key determinants within a unified framework tailored to emerging economies.